Movimento dirigido ao alvo do membro superior ipsilesional em indivíduos com ombro doloroso hemiplégico - Borges, Heloise Cazangi (2020)
Background: Hemiplegic shoulder pain is common after stroke. The pain perception may exacerbate changes in motor behavior of the ipsilesional upper limb, contributing to the functional decline of the individual’s motor perfomance. Objective: To evaluate the influence of pain perception on the aiming movements performed with the ipsilesional upper limb in individuals with unilateral chronic stroke. Methods: A cross-sectional study was conducted with 41 participants divided into three groups: stroke with contralesional shoulder pain ≥ three by Visual Numerical Pain Scale (SSP; n=13), stroke without shoulder pain (SnSP; n=14) and healthy control (CT; n=14), matched for gender and age. Individuals with stroke were matched for the severity of sensorimotor impairment by the Fugl-Meyer upper limb subscale and the injured hemisphere. Participants performed aiming movements with the ipsilesional upper limb, and with the corresponding limb for the CT group, with a cursor on the sensitive surface of a digitizing tablet. Performance between groups was compared by one-way analysis of variance, considering time of injury as a covariate. The planning and execution variables were analyzed, and a significance of 5% adopted. Results: SSP were slower (p = 0.010), less smooth (p = 0.002), had greater initial direction error (p = 0.002) and lower accuracy (p = 0.038) than the CT group, but were able to maintain movement precision. Conclusions: The perception of pain brings impairment to the performance of aiming movements performed with the ipsilesional upper limb in individuals with unilateral chronic stroke.